(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, special attention is paid to the concept of the concept and the definitions given to it, its formation in the world and Uzbek linguistics. National features of the content of the concept of health are interpreted linguistically. In addition, the scientific article contains some comments on the relationship of words, concepts and concepts, as well as on their general and special features. In the article, the word "disease" is considered the dominant word among its synonymous (synonymous) words, and these words include "unhealthy", "unhealthy", "disease" (doctors recommend using this word), "disease". Units such as pain, weakness (weakness) were analyzed by examples. It turned out that there are no replacement synonyms for the word health. They differ significantly in meaning. (feeling, state) or has a bright stylistic coloring (health, health). The words health and disease are included in the semantic field called "feeling", which may also include their synonyms, the above-mentioned and semantically close units, as well as the medical term "premorbid state". As a result of the study of the concept of "health", this concept includes the absence of diseases, a healthy lifestyle, spiritual and moral lifestyle, physical health, complete satisfaction with lifestyle and maturity. The article notes that it covers such conceptual units as endurance, physiological and biological healthy lifestyle.